Individual Assessment to Develop Employees' Careers at Company X - Ufaira, Rifda Alda; Gusria , Amarisma; Fadhli, Muhammad (Philanthropy: Journal of Psychology, 2025)
The success of an organization hinges on the importance of alocating the right resources to it. Organizations are expected to pay attention to the suitability between employees and their work through individual assessments with psychological examinations. In addition to looking at the suitability of employees' potential or competencies with the demands of their jobs, organizations should also measure the suitability of employees' career interests with the choice of employees' job aspirations using Holland's RIASEC test. The research in the form of the application of individual assessment of career development was carried out on subjects who felt bored or were not suitable for their current job. Data analysis uses descriptive qualitative methods. The results of the study show that the potential or competence of the subject is in accordance with their work, so they are expected to be able to perform optimally at work. However, the subject's career interests do not match his career aspirations or the job he wants, so it is expected that individuals can develop their career interests in other activities, as well as the organization can take other development steps, such as work rotation.